Genome organization and genomics in Chlamydia: whole genome sequencing increases understanding of chlamydial virulence, evolution, and phylogeny - Luu, Laurence Don Wai; Kasimov, Vasilli; Phillips, Samuel; Myers, Garry S. A.; Jelocnik, Martina (Frontiers in Cellular and Infection Microbiology, 2023)
The genus Chlamydia contains important obligate intracellular bacterial pathogens to humans and animals, including C. trachomatis and C. pneumoniae. Since 1998, when the first Chlamydia genome was published, our understanding of how these microbes interact, evolved and adapted to different intracellular host environments has been transformed due to the expansion of chlamydial genomes. This review explores the current state of knowledge in Chlamydia genomics and how whole genome sequencing has revolutionised our understanding of Chlamydia virulence, evolution, and phylogeny over the past two and a half decades. This review will also highlight developments in multi-omics and other approaches that have complemented whole genome sequencing to advance knowledge of Chlamydia pathogenesis and future directions for chlamydial genomics.